2010
DOI: 10.1111/j.1365-2249.2010.04273.x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of patients with type 1 diabetes transplanted with neonatal pig islets

Abstract: SummaryPancreas transplantation is an option to achieve better metabolic control and decrease chronic complications in patients with diabetes. Xenotransplantation becomes an important alternative. In this study, we show the clinical outcome of patients with type 1 diabetes transplanted with neonatal pig islets without immunosuppression. In a longitudinal study of 23 patients with type 1 diabetes, who received porcine islets between 2000 and 2004, we registered demographic and clinical characteristics every 3 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 32 publications
4
45
0
Order By: Relevance
“…Besides nurturing these autoimmunogenic germ cells, SCs also protect them from an immunologic response by expressing and secreting several immunoregulatory factors, thus contributing to testis' immune privilege. Immune modulation by SCs is not restricted to the testis as SCs also survive when transplanted to ectopic sites (outside the testis), across immunological barriers (i.e., allo-or xenotransplantation), without the need for immunosuppressive drugs [5][6][7][8][9][10][11][12][13]. This suggests that immune-privileged SCs used as a vehicle for cell-based gene therapy have the potential to overcome the obstacle of immune rejection.…”
Section: Introductionmentioning
confidence: 96%
“…Besides nurturing these autoimmunogenic germ cells, SCs also protect them from an immunologic response by expressing and secreting several immunoregulatory factors, thus contributing to testis' immune privilege. Immune modulation by SCs is not restricted to the testis as SCs also survive when transplanted to ectopic sites (outside the testis), across immunological barriers (i.e., allo-or xenotransplantation), without the need for immunosuppressive drugs [5][6][7][8][9][10][11][12][13]. This suggests that immune-privileged SCs used as a vehicle for cell-based gene therapy have the potential to overcome the obstacle of immune rejection.…”
Section: Introductionmentioning
confidence: 96%
“…Sertoli cells were also able to enhance survival of islets graft in xenogeneic recipients [171173] . Finally, coencapsulated porcine islets and Sertoli cells were implanted into human subjects in a controversial Mexican clinical trial [8,174,175] . Some of the transplanted patients experienced reduction in their requirements for insulin therapy for up to 3 years.…”
Section: Controlling Inflammationmentioning
confidence: 99%
“…Interestingly all patients improved glycemic control after transplantation irrespective of the amount of insulin reduction. Long-term follow-up of those patients revealed that all patients have positive porcine C-peptides in urine (Valdes-Gonzalez et al, 2010). In terms of safety, routine microbiological screening of all patients and close family have been consistently negative, although two patients exhibited transient chimerism as evidenced by porcine DNA thru polymerase chain reaction (PCR).…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…Especially, creating a new viral disease by xeno-transplantation must be avoided. Infection of porcine endogenous retrovirus after xeno-transplantation into immune compromised mice demonstrated the risk of the combination of immunosuppression and xenotransplantation (van der Laan LJ et al, 2000). Therefore current bio-artificial islet transplantations have been performed without immunosuppression.…”
Section: Standardmentioning
confidence: 99%